2017
DOI: 10.3390/healthcare5040091
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Differences in Psychosocial Factors of Perinatal Depression: A Systematic Review of India and Japan

Abstract: Perinatal depression is prevalent worldwide. However, there are few available studies that discuss the different cultural factors affecting perinatal depression within Asian countries. This study aims to compare the literature regarding related factors relating to perinatal depression in India and Japan, and to synthesize the evidence common to both countries in addition to the country-specific evidence. We conducted a systematic review using several databases (CINAHL, MEDLINE, Pubmed, Ovid, SCOPUS, IndMED, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 68 publications
(90 reference statements)
0
24
3
Order By: Relevance
“…The mothers who conceived after infertility treatment do not have any gender preference in comparison to naturally conceived mother, as such a baby is precious to them. 9 In our study, partner support was not significantly influencing the early postpartum depression as the immediate primary caregivers for mothers are better in Indian culture following delivery, whereas it might influence at a later part of the postpartum period where mothers are expected to return to their husband's family. 16,22 A study done by Tendais et al found no change in postpartum anxiety score between mothers who conceived spontaneously versus postinfertility treatment group with regard to multiple births of the baby.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The mothers who conceived after infertility treatment do not have any gender preference in comparison to naturally conceived mother, as such a baby is precious to them. 9 In our study, partner support was not significantly influencing the early postpartum depression as the immediate primary caregivers for mothers are better in Indian culture following delivery, whereas it might influence at a later part of the postpartum period where mothers are expected to return to their husband's family. 16,22 A study done by Tendais et al found no change in postpartum anxiety score between mothers who conceived spontaneously versus postinfertility treatment group with regard to multiple births of the baby.…”
Section: Discussioncontrasting
confidence: 55%
“…The mothers who conceived after infertility treatment do not have any gender preference in comparison to naturally conceived mother, as such a baby is precious to them. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in Japan. [21] This may be because women feel more secure and safe in such positive environment; good care of pregnant women and more helping hands are there to take care of the newborn, which reduces the stress of the mother and she can have sufficient rest. Such association between support from in-laws and depression is also seen in a study by Gupta et al .,[12] Bener et al .,[15] and Morikawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…The impact is noted to be higher on women in low- and middle-income countries [ 15 ]. In addition to biological vulnerability to major depression, low social support, interpersonal conflict, and difficulties in role transition and gender inequality are important risk factors leading to perinatal depression [ 18 – 20 ].…”
Section: Discussionmentioning
confidence: 99%